PENGARUH PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS PUISI KELAS V SDN 13 PONTIANAK BARAT - Cindi Ayu Fernanda; Siti Halidjah; Sugiyono Sugiyono (Universitas Tanjungpura, 2019)
AbstractThe purpose of this research was to analyze the effect of the Cooperative Learning Type Picture and Picture on the poetry writing skills of fifth grade students at the 13th Elementary School in West Pontianak. The research method used is an experimental, Non-Equivalent Group Design type Quasi Experimental form. The research population was all students of class V Elementary School 13 West Pontianak, totaling 72 students. The sampling technique uses probability sampling while the sample is the VA class as an experimental class with 35 students and the VB class as a control class with 37 students. The data collection technique used the measurement technique. Data collection tools are written tests in the form of essays. The results of data analysis namely, the average score of the control class post-test was 69.18 and the experiment was 78.28. Based on the results of t-test calculations obtained tcount 3.146 > t table 1.98, then Ha is accepted. This shows that there is an influence in the poetry reading skills of the control class students with the experimental class. Calculation of effect size of 0.83 (high criteria).Keywords: Influence, Picture and Picture, Poetry Writing Skills.